Effect of innovative technology using staves and micro-oxygenation on the odorant and sensory profile of aged wine spirit. (15th December 2020) - Granja-Soares, J.; Roque, Rita; Cabrita, M.J.; Anjos, Ofélia; Belchior, A.P.; Caldeira, Ilda; Canas, Sara
Highlights: Innovative technology for wine spirit ageing. Traditional versus alternative wine spirit ageing on odorants and sensory profile. Ageing system has greater impact on wine spirit than the type of wood. Micro-oxygenation combined with the staves enhances wood odorant compounds extraction. Chestnut wood staves combined with micro-oxygenation had the greatest impact on wine spirit composition. Abstract: The aged wine spirit is a beverage with great aromatic complexity. Their volatile compounds with odorant power coming from the distillate and from the wood used in its ageing, and the interactions that take place in the process, enhanced by oxygen, all contribute to this complexity. Due to time and cost inherent of ageing wine spirits in wooden barrels, research has sought to develop more sustainable alternatives to do it. In this context, the present study compares, the effect of traditional (wooden barrel) and alternative system (stainless steel tank with dipped staves and micro-oxygenation), on the odorant and sensory profile of a wine spirit, using Limousin oak and chestnut wood, after 12 months of ageing. The results suggest that the ageing process is accelerated by the alternative ageing technology and the chestnut wood, and the corresponding wine spirits presented characteristics of greater sensory evolution and strong wood compounds extraction.